Electronically Prescribing: A New Policy in Iranian Hospitals: Electronically Prescribing - Mohammad Khammarnia; Fatemeh Setoodehzadeh (Iranian Journal of Pharmaceutical Sciences, 2017)
Medication Errors (MEs) as one of the most important medical errors in hospitals are common, expensive, and sometimes harmful to patients. Several strategies, such as Computerized Provider Order Entry (CPOE) and wristband barcoding are used for decreasing MEs. The role of new technologies is emphasized in the policies and planning in the health system in Iran. Worldwide, CPOE is a new technology to improve patients’ care and safety, increase patients’ satisfaction and user productivity, decrease MEs and costs in hospitals. This system appears as an effective tool in reducing MEs. Elimination of eligibility errors, ensuring completeness in prescribing fields, and reduction in transcription errors are other benefits of CPOE system. CPOE has been implemented in Namazi Teaching Hospital and had impressive impact on the reduction of MEs. The use of this system is changing to a policy in hospitals in Iran and it is emphasized in the vision of Iran for 1404.